Impact of Health Expenditures on Labor Force Participation: Evidence from Pakistan - Rauf, Abdur; Bashir, Maryyum; Asif, Kiran; Saleem, Sardar Fawad (Asian Journal of Economic Modelling, 2018)
The current study focused on health expenditures and labor force participation linkages taking Pakistan as a sample case. Data sample cover the period from 1972 to 2013. Economic survey of Pakistan and WDI were consulted for data collection and the estimated results were extracted by using Autoregressive Distributive Lag Model which revealed that there is positive association between health and labor force participation rate in Pakistan. Amongst the other variables, secondary school enrolment and Investment also has positive impacts on labor force participation in both long and short span of time. Life expectancy has adverse effects and trade openness is insignificant in a model. It is suggested that to encourage higher labor force participation government may increase its expenditures on basic health issues along with investment friendly policies. Furthermore it is also suggested that education may also be encouraged for productive labor in a country.